Mental arrangement in cognitive processes, processing information accurately, and performing the skill of shooting from both sides in basketball - Kumar, Rajesh; Amer, Ahmed (Journal of Physical Education, 2024)
Basketball is considered an open-surface game that requires the player to deal with the variables of the match according to the movement or stability of the opponent and in the form of motor responses and accuracy and the arrival of the balls to the different playing areas in which the teammate is present to obtain an appropriate opportunity for the process of possession and control of the course of the game that qualifies the team to win the game. Or achieve the required points in the matches. The response is the motor ability that a basketball player needs. It takes a short time to execute, provided that this execution is distinguished by the element of accuracy, which comes from the mental arrangement of cognitive processes through which information related to the details of the technical performance of skills, especially the skill of lateral shooting in basketball, is prepared. The research aims to identify the role of mental arrangement in cognitive processes and prepare information for the accuracy of performing the skill of shooting from both sides of the basket among young players. It is assumed that there is a statistically significant correlation between mental arrangement in cognitive processes and preparing information for the accuracy of performing shooting from both sides of the basket for the youth group, and it was the research sample was 30 young players from the Al-Zafaraniya Youth and Sports Center, Diyala Bridge, and the municipalities in Baghdad - Al-Rusafa. The descriptive approach was adopted using the method of correlational relations, and the researcher used statistical methods, percentages, correlation coefficient (Pearson), arithmetic mean, and standard deviation to reach the results, and the results were presented. Analyzing and discussing the results, and arriving at the most important conclusions, there is a significant correlation between the mental arrangement in the cognitive processes and processing of information and the accuracy of shooting from both sides of the basket for the youth group. It is recommended to emphasize the mental arrangement in the cognitive processes and processing of information, provided that it is coupled with the accuracy of shooting side tackles with the ball. Basketball for young players.